Simple new technique for macular pucker peel without forceps - Lumi, Xhevat; Petrovski, Beáta Eva; Petrovski, Goran (Frontiers in Medicine, 2022)
Purpose This study aimed to describe the effectiveness and evaluate the anatomical and functional results of surgery for macular pucker (MP) peel using a 25-gauge pars plana vitrectomy (PPV) cutter without forceps. Methods This study assessed a prospective consecutive case series of 14 eyes of 14 patients who underwent 25-gauge PPV for MP. The surgical procedure was performed using the new peeling technique. The edge of the membrane was engaged at the opening of the cutter by gradually increasing the vacuum. The peeling process was finished by holding a stable vacuum or regrasping the membrane in the same manner. Results The study included six women and eight men patients with a mean age of 72.3 (range 59–84) years. MP peel was achieved in all cases without the need for microforceps. Patients were followed for at least 6 months. Visual acuity and retinal thickness were obtained 6 months after the surgery. Best corrected visual acuity improved from a mean pre-operative 0.6 on a logMAR scale to post-operative 0.23 (P < 0.001). Mean pre-operative Central Retinal Thickness was significantly reduced from 489.7 to 377.6 μm post-operatively (P < 0.001). There were no intra- or post-operative complications. Conclusion MP peel with a 25-gauge vitrectomy probe could be an alternative simple and safe technique. The technique does not require extra instrumentation. It results in anatomic and functional improvement in all cases.